2011
DOI: 10.1002/pip.1122
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high growth rates on evaporated Cu(In,Ga)Se2 layers and solar cells

Abstract: Thin film solar cells based on polycrystalline Cu(In,Ga)Se2 were prepared by elemental co‐evaporation using modified three‐stage processes on soda lime glass substrates at a low substrate temperature of 450°C intended for application on polyimide foils. The growth rates in the different stages of the growth process were varied, and it was observed that the final composition profile and structural quality of the film are mainly determined by the growth rate in the third stage. Application of high growth rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…All the samples showed the prominent peak corresponding to the A 1 optical phonon vibrational mode of chalcopyrite crystal structure. 24 As Ga content increases, the peak position is shifted to higher wavenumber. The same behavior was found by Olejnicek et al 19 Figures 5(a)-(e) shows FE-SEM micrographs of the synthesized CIGS nanoparticles with varying x values from 0 to 1.…”
Section: Resultsmentioning
confidence: 97%
“…All the samples showed the prominent peak corresponding to the A 1 optical phonon vibrational mode of chalcopyrite crystal structure. 24 As Ga content increases, the peak position is shifted to higher wavenumber. The same behavior was found by Olejnicek et al 19 Figures 5(a)-(e) shows FE-SEM micrographs of the synthesized CIGS nanoparticles with varying x values from 0 to 1.…”
Section: Resultsmentioning
confidence: 97%
“…The main process parameters investigated in this work which determine the overall grading profile are (i) the deposition rate in the 3rd stage which was reduced significantly and (ii) the amount of Cu‐excess reached at the end of the 2nd stage, which was increased from 10 to about 15%. Previous work on low‐temperature grown CIGS has shown that increasing the growth rate in the 3rd stage leads to a much more pronounced grading profile near the surface as well as to significantly hindered crystallization 12, 13. Therefore, the deposition rate in the 3rd stage was reduced to enhance the structural quality of the CIGS film.…”
Section: Resultsmentioning
confidence: 99%
“…In a next step, CIGS was deposited by co‐evaporation of Cu, In, Ga, Se elements with a modified three‐stage process. The details of the deposition process are given elsewhere . Two different nominal maximum substrate temperatures of 475°C (LT) and 600°C (HT) were used.…”
Section: Methodsmentioning
confidence: 99%